Study of Damietta branch meander suitability for inland first-class river cargo transportation - W.A. Fahmy; Nasr Hekal (Journal of King Saud University: Engineering Sciences, 2023)
The current research aims to study the suitability of Damietta branch meanders for safe first-class cargo transportation. This branch is the River Nile eastern waterway bifurcated at the beginning of the Delta region, which is about 22.0 km downstream of El-Roda gauge in Cairo. It extends for 244 km to the Mediterranean Sea. The branch plan form was examined for meanders. Fifty-one meanders could be identified throughout. Their characteristics were analyzed. The results revealed the existence of eight sharp meanders and seven critical looping ones that would slow down and jeopardize the first-class navigation traffic. Also, it was found that about 68 % of the looping meander lengths could be saved if cut-offs were executed. Accordingly, examples of straightening the river at four meanders were proposed for clarification. It was found that their lengths could be reduced by 51.10 %. Finally, the study concluded that in order for the Damietta branch to be qualified and entitled to safe first-class cargo transportation, the sharp meanders and critical loops have to be subject to training works and re-channelized.